2006
DOI: 10.1051/0004-6361:20053367
|View full text |Cite
|
Sign up to set email alerts
|

The Large Magellanic Cloud: diffuse interstellar bands, atomic lines and the local environmental conditions

Abstract: The Large Magellanic Cloud (LMC) offers a unique laboratory to study the diffuse interstellar bands (DIBs) under conditions that are profoundly different from those in the Galaxy. DIB carrier abundances depend on several environmental factors, in particular the local UV radiation field. In this paper we present measurements of twelve DIBs in five lines of sight to early-type stars in the LMC, including the 30 Doradus region. From the high resolution spectra obtained with VLT/UVES we also derive environmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 84 publications
9
102
1
Order By: Relevance
“…In Figure 2, all four stars either have weak DIB strengths or strong far-UV curvature. The Large Magellanic Cloud shows a similar general relationship between DIB strength and reddening as is seen in the Galaxy (Cox et al 2006). The Small Magellanic Cloud is more interesting.…”
Section: Dibs and Uv Extinctionsupporting
confidence: 59%
“…In Figure 2, all four stars either have weak DIB strengths or strong far-UV curvature. The Large Magellanic Cloud shows a similar general relationship between DIB strength and reddening as is seen in the Galaxy (Cox et al 2006). The Small Magellanic Cloud is more interesting.…”
Section: Dibs and Uv Extinctionsupporting
confidence: 59%
“…We start by noting that W(λ5797)/W(λ5780) is a variable that is clearly related to physical conditions, and has in particular been linked to the amount of exposure to the ambient UV radiation field (see e.g. Kre lowski & Sneden 1995;Herbig 1995;Cami et al 1997;Sonnentrucker et al 1997;Kre lowski et al 1999;Vuong & Foing 2000;Cox et al 2006;Friedman et al 2011;Vos et al 2011). More specifically, these studies have shown that the λ5780 DIB is weak in shielded environments, but becomes significantly stronger with increasing UV exposure in diffuse clouds; the λ5797 DIB on the other hand is already strong in shielded environments, and is largely indifferent to UV exposure in most diffuse clouds.…”
Section: N(h) and E(b-v)mentioning
confidence: 99%
“…Seab & Snow 1984;Herbig 1993;Cami et al 1997;McCall et al 2010;Friedman et al 2011) -and research into the environmental behavior of the DIBs (e.g. Jenniskens et al 1994;Cami et al 1997;Sonnentrucker et al 1997;Cox et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A number of DIB observational studies have been published in the last two decades such as DIB surveys (e.g., Herbig 1995, Jenniskens & Désert 1994, Tuairisg et al 2000, Hobbs et al 2008; measurements of DIB families, correlations and environment dependences (e.g., Cami et al 1997, Kre lowski et al 1999,Ádámkovics et al 2005 and extragalactic DIBs (Ehrenfreund et al 2002, Cox et al 2006. Resolved substructures were detected (e.g., Sarre et al 1995, Ehrenfreund & Foing 1996) and compared to predicted rotational contours of large molecules (Cossart-Magos & Leach 1990).…”
Section: Surveys and Environmental Studiesmentioning
confidence: 99%
“…This IP is reminiscent of PAHs or fullerene cations, and could explain the correlation of DIBs with Ca + column densities and velocities. From a survey of DIBs in Rho Oph (Vos et al 2011) the Magellanic Clouds (LMC/SMC), Ehrenfreund et al (2002), Cox et al (2006Cox et al ( , 2007b measure a weakening of DIBs as result of UV field and low metallicity. Ehrenfreund & Foing (1996) modelled the observed substructures of the 5797, 6379 and 6613Å DIBs using rotational contours of large molecules indicating a peak separation of 4B J max = 4(kT B/2) 1/2 and contour wing width = kT dB/2B.…”
Section: Surveys and Environmental Studiesmentioning
confidence: 99%